Biuletyn Dolnośląski . pismo Klubu Samoobrony Społecznej we Wrocławiu, 23 August 1980 (Wydanie Specjalne) - Morawiecki, Kornel; Waszkiewicz, Jan; Ewaryst, Jan; Twaed.owski, Marek; Gorbanevskaja, Natal'ja; Prus, Marcin; Besançon, Alain; Gwiazda, Andrzej; Wierzyński, Michał; Jaworski, Rafał; Teliga, Józef; Myślecki, Wojciech; et al. ([Klub Samobrony Społecznej], 1980)
Print run: 2000-10000 copies